Analysis of the Influence of Content Creators, Social Media, and Website Quality on Purchasing Decisions at Kyou Hobby Shop - Candra Lucas Diansa Putra; Alshaf Pebrianggara; Bayu Hari Prasojo; M. Rizal Yulianto (Publikasi Indonesia, 2026)
The rapid growth of Japanese pop culture and the increasing popularity of anime merchandise have significantly influenced consumer behavior, particularly among Generation Z in Indonesia. The development of digital platforms has also transformed marketing strategies, where content creators, social media, and website quality play crucial roles in shaping consumer purchasing decisions. This study aims to analyze the influence of content creators, social media, and website quality on purchasing decisions at Kyou Hobby Shop. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z consumers who had purchased products from Kyou Hobby Shop. The minimum sample consisted of 96 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. Several statistical tests were conducted, including validity, reliability, classical assumption tests, t-tests, and coefficient of determination analysis. The results indicate that content creators, social media, and website quality all have a positive and significant influence on purchasing decisions. Among these variables, website quality shows the strongest effect on consumer purchasing behavior. The findings also reveal that the three independent variables collectively explain 74.3% of the variation in purchasing decisions. In conclusion, an integrated digital marketing strategy involving effective content creators, active social media engagement, and high-quality website performance is essential for improving consumer purchasing decisions at Kyou Hobby Shop.